Peminggiran Perempuan dalam Kuasa Kelahiran dan Perkembangan Dolalak - Sofa Marwah; Soetji Lestari; Tri Rini Widyastuti (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
The oral history of the birth of dolalak dance differs from other traditional dance legends in Java, such as ronggeng, lengger or tayub. The birth of the traditional dances is related to female figures. The dolalak dance was invented by native soldiers (male) during the Dutch colonial period. This paper aims to examine  dolalak as an arena of power and the contribution of women to dolalak in the context of historical reflection. This research is a qualitative study that uses data collection techniques by interviewing, observing, and is supported by documentation studies as well as related previous research. The results of this study show that dolalak becomes the arena of power in its invention. There is a major power in interpreting the invention of dolalak, namely by soldiers (men). As for its development, the dolalak becomes an arena for power struggles that surrounds it. The dolalak is performing art. The dolalak also a medium for spreading Islam, and then the power by the state over it. The power struggles of dance operate and be practiced, from one meaning to another, until the power of state enters. It strengthens the theorization of power. It will continue as a practice of power. In this context, the contribution of women as figures preserving the dance is vulnerable to the invisible. Dolalak dance is mostly performed by female dancers and this has become an icon for people in Purworejo Regency, Central Java. Therefore, it is time for women as traditional dance preservers to be narrated and fill in public knowledge.